Kepuasan Mahasiswa Terhadap Kualitas Layanan Administrasi Sekolah Tinggi Ilmu Administrasi Karya Dharma Merauke - Pohan, Farida Romaito; Wibowo, Juventus Bangkit; Ningrum, Nur Rohmah Yulia (Jurnal Administrasi Karya Dharma, 2024)
This research aims to determine the level of student satisfaction with the quality of administrative services at STIA Karya Dharma Merauke. This research is a descriptive quantitative study using survey methods. The data collection technique used is a questionnaire. The population of this study is all active students for the academic year 2023/2024, totaling 478 students. The sampling technique used is simple random sampling, and a sample of 83 students was obtained. The data analysis technique used is the Community Satisfaction Index (CSI), in this case, students. The research results show that student satisfaction based on direct evidence indicators generally has an average score of 60.17, which falls into the Fair category. Student satisfaction based on the responsiveness indicator falls into the good category with an average score of 67.85. The Reliability Indicator with an average score of 79.72 falls into the Good category. The Empathy Indicator with a score of 78.82 falls into the Good category. The service procedure indicator with a score of 79.07 falls into the Good category. The Justice Indicator received a service score of 80.42, which falls into the Good category. Meanwhile, the environmental comfort indicator received a score of 60.24, which falls into the Satisfactory category. On the service security indicator, the score is 76.20, categorized as Good. Overall, student satisfaction with the quality of administrative services at STIA Karya Dharma Merauke falls into the good category